Remote magnetic catheter navigation versus conventional ablation in atrial fibrillation ablation: Fluoroscopy reduction. Issue 3 (10th November 2016) - Lim, Paul Chun Yih; Toh, Joseph Jia Hong; Loh, Julian Kenrick Xing Yuan; Lee, Edward Chun Yi; Chong, Daniel Thuan Tee; Tan, Boon Yew; Ho, Kah Leng; Ching, Chi Keong; Teo, Wee Siong
Abstract: Background: Percutaneous transcatheter radiofrequency ablation of atrial fibrillation with remote controlled magnetic navigation (RMN) has been shown to reduce radiation exposure to patients and physicians compared with conventional manual (MAN) ablation techniques. Methods: Catheter ablation for atrial fibrillation was performed utilizing RMN in 214 consecutive patients and MAN ablation techniques in 229 patients. We compared the fluoroscopy and procedural times between RMN and MAN catheter ablation of atrial fibrillation. Secondary objectives included comparing acute procedural success and short‐term complication rates between both ablation strategies. Results: Fluoroscopy time was significantly shorter in the RMN group than the MAN group (53.5±30.1 vs 68.1±27.6 min, respectively; p <0.01); however, the total procedural time was longer in the RMN group (280.2±74.4 min vs 213.1±64.75, respectively; p >0.001). Further subgroup analysis of the most recent 50 ablations each from the RMN and MAN groups, to attenuate the RMN learning curve effect, showed an even greater difference in fluoroscopy time (RMN vs MAN: 53.5±30.1 vs 68.1±27.6 min), though a consistently longer procedure time with RMN (249.5±65.5 vs 186.3±65.6 min, respectively). The acute procedural success rate was comparable between the groups (98.6% vs 95.6%, respectively; p =0.07). The rates of acute complications were similar in both groups (2.3% vs 4.8%, respectively; p =0.16). Conclusions: In radiofrequency ablation of atrial fibrillation, RMN appears to significantly reduce fluoroscopy time compared with conventional MAN ablation, though at a cost of increased total procedural time, with comparable acute success rates and safety profile. A reduction in procedure and fluoroscopy times is possible with gaining experience.